Relation of Global Solar Radiation with Temperature, Rainfall, Sunshine Duration and Clearness Index at Western Himalayan Region, Nepal - KC, Bed Raj; Gurung, Shekhar (Journal of Advanced Academic Research, 2020)
The global solar radiation is measured at the horizontal surface by calibrated pyranometer at Jumla(29.27°N to 82.18°E, 2514.0m). The effect of different physical as well as meteorological parameters to the intensity of global solar radiation was analyzed. This paper compares global solar radiation with sunshine duration, temperature, and rainfall and clearness index. This paper also explains the monthly, seasonal variation of global solar radiation. The annual average global solar radiation is 18.36MJ/m2 /day which is sufficient to promote solar active and passive solar energy technology at Himalaya terrain Jumla and other similar geographical locations. This novel result can be used for location of similar meteorological and geographical characteristics at which solar data are not available.